2015
DOI: 10.1098/rsif.2014.1412
|View full text |Cite
|
Sign up to set email alerts
|

Linking morphodynamics and directional persistence of T lymphocyte migration

Abstract: T cells play a central role in the adaptive immune response, and their directed migration is essential for homing to sites of antigen presentation. Like neutrophils, T lymphocytes are rapidly moving cells that exhibit amoeboid movement, characterized by a definitive polarity with F-actin concentrated at the front and myosin II elsewhere. In this study, we used total internal reflection fluorescence (TIRF) microscopy to monitor the cells' areas of contact with a surface presenting adhesive ICAM-1 and the chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…B cells migrating on CXCL13 and ICAM-1 showed the characteristic amoeboid morphology and fast movement (average translocation speed ≈ 14 μm/min), consistent with previous studies (10, 12); however, the dilation/shrinking dynamics reported here is a new insight revealed using TIRF microscopy. This is distinct from the leading-edge dynamics reported for other fast-moving amoeboid cells, such as Dictyostelium discoideum and T lymphocytes (29, 3638). Our analysis showed independent dilation/shrinking waves on the two sides of the cell front.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…B cells migrating on CXCL13 and ICAM-1 showed the characteristic amoeboid morphology and fast movement (average translocation speed ≈ 14 μm/min), consistent with previous studies (10, 12); however, the dilation/shrinking dynamics reported here is a new insight revealed using TIRF microscopy. This is distinct from the leading-edge dynamics reported for other fast-moving amoeboid cells, such as Dictyostelium discoideum and T lymphocytes (29, 3638). Our analysis showed independent dilation/shrinking waves on the two sides of the cell front.…”
Section: Discussioncontrasting
confidence: 85%
“…Our analysis showed independent dilation/shrinking waves on the two sides of the cell front. Our conclusion is that the balance between dilation/shrinking at the edges determines cell migration directionality, which stands in contrast to the bifurcation of protrusions that characterizes migration of primary T lymphocytes on CXCL12/ICAM-1 (29); the leading edge dynamics in B cells is more reminiscent of the instabilities associated with turning of fish keratocytes (39). …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, Gorelik and Gautreau have recently suggested that arpin [63] may induce cells to turn by slowing them [12]; this is consistent with our result that slowing the cell (or decreasing the Peclet number) can cause turning. However, we emphasize that in other cell types turning is associated with different morphology and may not be controlled by the simple mechanism studied here [64]. …”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that ICAM-1 is an important adhesion molecule belonging to the immunoglobulin superfamily. ICAM-1 is involved in neutrophil chemotaxis by binding with the surface ligand CD11/CD18 on neutrophils and lymphocytes (Dominguez et al, 2015;Liu et al, 2015;Sumagin and Parkos, 2015). MIP-2 belongs to the chemokine C-X-C subfamily and induces marked chemotaxis in neutrophils and lymphocytes (Takahashi et al, 2009;Tateno et al, 2013;Vagima et al, 2015).…”
Section: Discussionmentioning
confidence: 99%